The predictors of outcome in patients that require management in intensive care units: A narrative review - İbrahim Karagöz; Bahri Özer; Gulali Aktas (Hitit Medical Journal)

(untitled)
Intensive care units stand as the frontline battlegrounds where medical warriors combat the most critical illnesses and injuries. Within the labyrinth of intensive care units, where every moment teeters between life and death, prognostic markers emerge as beacons of guidance amidst uncertainty. In recent years, researchers have identified several novel mortality predictors in the intensive care population. In this review, we aimed to examine the clinical and laboratory markers that have been proposed in recent years to evaluate prognosis in the intensive care unit population and to review the literature on this topic. Management of patients in intensive care units is a dynamic process and reliable risk stratification models and prognostic markers are needed for this purpose. Novel prognostic indicators could serve as reliable diagnostic and prognostic tools in critically ill patients.